Hilbert Spaces I: Basic Properties

Hilbert Spaces I: Basic Properties

HS I c Gabriel Nagy Hilbert Spaces I: Basic Properties Notes from the Functional Analysis Course (Fall 07 - Spring 08) In this section we introduce an important class of Banach spaces, which carry some additional geometric structure, that enables us to use our two- or three-dimensional intuition. Convention. Throughout this note all vector spaces are over C. A. Algebraic Preliminaries: Sesquilinear Forms Definition. Given two vector spaces X and Y, a map φ : X × Y → C is said to be a sesquilinear form on X × Y, if: • for every x ∈ X , the map Y 3 y 7−→ φ(x, y) ∈ C is linear; • for every y ∈ Y, the map X 3 x 7−→ φ(x, y) ∈ C is conjugate linear, meaning that the conjugate map X 3 x 7−→ φ(x, y) ∈ C is linear. Exercise 1♥. Given a sesquilinear form φ on X × Y, prove that the map ? φ : Y × X 3 (y, x) 7−→ φ(x, y) ∈ C is a sesquilinear form on Y × X . This map is referred to as the adjoint of φ. For the remainder of this sub-section we are going to restrict our attention to the case when X = Y. In this case Lemmas 1-3 contain three easy but fundamental results. Lemma 1 (The Parallelogram Law). If X is a vector space and φ : X × X → C is a sesquilinear form, then φ(x + y, x + y) + φ(x − y, x − y) = 2φ(x, x) + φ(y, y), ∀ x, y ∈ X . (1) Proof. This follows directly, using the properties of sesquilinear forms, which yield φ(x + y, x + y) = φ(x, x) + φ(x, y) + φ(y, x) + φ(y, y), φ(x − y, x − y) = φ(x, x) − φ(x, y) − φ(y, x) + φ(y, y), for all x, y ∈ X . Lemma 2 (The Polarization Identity). If X is a vector space and φ : X × X → C is a sesquilinear form, then 3 1 X φ(x, y) = i−kφ(x + iky, x + iky), ∀ x, y ∈ X . (2) 4 k=0 1 Proof. Denote by T4 the set of roots of unity of order 4, that is, T4 = {±1, ±i}, so that the sum in the right-hand side of (2) simply reads P ζφ¯ (x + ζy, x + ζy). ζ∈T4 By the properties of sesquilinear forms, we have φ(x + ζy, x + ζy) = φ(x, x) + φ(ζy, x) + φ(x, ζy) + φ(ζy, ζy) = = φ(x, x) + ζφ¯ (y, x) + ζφ(x, y) + ζζφ¯ (y, y), ∀ x, y ∈ X , ζ ∈ C. If we specialize to the case when ζ ∈ T, i.e. |ζ| = 1(= ζζ¯ ), then the above calculation yields ζφ¯ (x + ζy, x + ζy) = ζφ¯ (x, x) + ζ¯2φ(y, x) + φ(x, y) + ζφ¯ (y, y), and then the sum in the right-hand side of (2) is: 3 X X X i−kφ(x + iky, x + iky) = ζ¯ · φ(x, x) + φ(y, y) + ζ¯2 · φ(y, x) + 4φ(x, y), k=0 ζ∈T4 ζ∈T4 so by the obvious identities P ζ¯ = P ζ¯2 = 0, the desired identity (2) follows. ζ∈T4 ζ∈T4 Definitions. Let X be a vector space, and let φ : X × X → C be a sesquilinear form. A. We say that φ is hermitian, if φ? = φ, which means: φ(x, y) = φ(y, x), ∀ x, y ∈ X . (3) B. We say that φ is positive definite, if: φ(x, x) ≥ 0, ∀ x ∈ X . (4) C. We say that φ is strictly positive definite, if: (i) φ is positive definite, and (ii) φ(x, x) = 0 ⇒ x = 0. Remarks 1-3. Let φ : X × X → C be a sesquilinear form. 1. The condition that φ is hermitian is equivalent to the condition: φ(x, x) ∈ R, ∀ x ∈ X . (5) The implication “hermitian” ⇒ (5) is trivial. Conversely, if φ satisfies (5), then (using the notations from the proof of Lemma 2), by the Polarization Identity we have 1 X 1 X φ(y, x) = ζφ(y + ζx, y + ζx) = ζφ(y + ζx, y + ζx), 4 4 ζ∈T4 ζ∈T4 so using the “change of variable” γ = ζ¯, we also get 1 X φ(y, x) = γ¯φ(y +γx, ¯ y +γx ¯ ), (6) 4 γ∈T4 2 and now the desired identity (3) follows from the properties of sesquilinear forms, which imply φ(y +γx, ¯ y +γx ¯ ) = φγ¯(x + γy), γ¯(x + γy) = = γγφ¯ (x + γy, x + γy) = φ(x + γy, x + γy), ∀ γ ∈ T4, so when we go back to (6), again by the Polarization Identity we get 1 X φ(y, x) = γφ¯ (x + γy, x + γy) = φ(x, y). 4 γ∈T4 2. If φ is hermitian, then it satisfies φ(x + y, x + y) = φ(x, x) + φ(y, y) + 2Re φ(x, y), (7) φ(x − y, x − y) = φ(x, x) + φ(y, y) − 2Re φ(x, y), (8) for all x, y ∈ X . These two identities are referred to as the Law of Cosine. 3. If φ is positive definite, then φ is hermitian. This follows immediately from Remark 1. Lemma 3 (Cauchy-Buniakowski-Schwartz Inequality). If φ : X × X → C, then |φ(x, y)|2 ≤ φ(x, x) · φ(y, y), ∀ x, y ∈ X . (9) Furthermore, if φ(x, x) 6= 0, then one has equality in (9), if and only if there exists ζ ∈ C, such that φ(ζx + y, ζx + y) = 0. (10) Proof. Fix x and y, and note that, by the Law of Cosine, one has 2 2 0 ≤ φ(αx + βy, αx + βy) = |α| φ(x, x) + 2Re αβφ¯ (x, y) + |β| φ(y, y), ∀ α, β ∈ C. (11) Fix now β ∈ C, with |β| = 1, such that βφ(x, y) = |φ(x, y)|, and define the function g : R 3 t 7−→ φ(tx + βy, tx + βy) ∈ R, which by (11) can equivalently be written as 2 g(t) = t φ(x, x) + 2t|φ(x, y)| + φ(y, y), t ∈ R. (12) By positive definiteness, we also know that g(t) ≥ 0, ∀ t ∈ R. (13) We now have two cases to consider: (i) φ(x, x) = 0; (ii) φ(x, x) > 0. In case (i) – when g is a polynomial of degree 1 – condition (13) forces g to be constant, so φ(x, y) = 0, and then (9) is trivial. In case (ii) it follows that g is a quadratic polynomial (with positive leading coefficient), so condition (13) forces the discriminant ∆ to be non-positive, i.e. 4|φ(x, y)|2 − 4φ(x, x) · φ(y, y) ≤ 0, from which (9) is trivial. Furthermore, if equality holds in (9), this means that 3 ∆ = 0, so the equation g(t) = 0 has a unique real solution t0, which means precisely that φ(t0x + βy, t0x + βy) = 0, so we also get ¯ ¯ ¯ ¯ ¯ φ(t0βx + y, tβx + y) = φ β(t0x + βy), β(t0x + βy) = ββφ(t0x + βy, t0x + βy) = 0, ¯ so (10) holds with ζ = t0β. Conversely, if (10) holds for some ζ, then by (9) it follows that 0 ≤ |φ(x, ζx + y)|2 ≤ φ(x, x) · φ(ζx + y, ζx + y) = 0, 0 ≤ |φ(y, ζx + y)|2 ≤ φ(y, y) · φ(ζx + y, ζx + y) = 0, which give φ(x, ζx + y) = φ(y, ζx + y) = 0, so we get φ(x, y) = −ζφ(x, x) and φ(y, y) = −ζφ(y, x) = −ζφ(x, y) = ζζφ¯ (x, x), thus clearly forcing |φ(x, y)|2 = |ζ|2φ(x, x)2 = φ(x, x) · φ(y, y). The final result in this sub-section establishes the characterization of positive definite sesquilinear forms in terms of convexity. Theorem 1. Let X be a C-vector space. For a map q : X → [0, ∞), the following are equivalent. (i) There exists a positive definite sesquilinear form phi : X × X → C, such that q(x) = pφ(x, x), ∀ x ∈ X . (14) (ii) q is a seminorm on X , which satisfies the Parallelogram Law: q(x + y)2 + q(x − y)2 = 2q(x)2 + 2q(y)2, ∀ x, y ∈ X . (15) Moreover, φ is unique and satisfies the Polarization Identity: 3 1 X φ(x, y) = i−kq(x + iky)2, (16) 4 k=0 Proof. (i) ⇒ (ii). Assume q is defined by (14), and let us prove first that q is a seminorm. Since φ(ζx, ζx) = ζζφ¯ (x, x) = |ζ|2φ(x, x), by taking square roots, it follows that q(ζx) = |ζ| · q(x), ∀ ζ ∈ C, x ∈ X . To prove the triangle inequality, we use the Law of Cosine and the Cauchy-Buniakowski- Schwartz Inequality, which gives: φ(x + y, x + y) = |φ(x + y, x + y)| = |φ(x, x)| + 2Re φ(x, y) + φ(y, y)| ≤ = |φ(x, x) + 2|φ(x, y)| + φ(y, y) ≤ ≤ φ(x, x) + 2pφ(x, x) · φ(y, y) + φ(y, y) = pφ(x, x) + pφ(y, y)2, so by taking square roots we get q(x + y) ≤ q(x) + q(y), ∀ x, y ∈ X . 4 The fact that q satisfies the Parallelogram Law (15), as well as the Polarization Identity (16) is immediate from Lemmas 1 and 2. (ii) ⇒ (i). Assume q be a seminorm that satisfies the Parallelogram Law (15), define φ : X × X → C by (16), and let us prove that φ is positive definite, and it also satisfies (14). Claim 1: φ(y, x) = φ(x, y), ∀ x, y ∈ X . Fix x, y ∈ X , so by definition, we have 3 1 X φ(y, x) = ikq(y + ikx)2. (17) 4 k=0 Since q is a seminorm, we have q(y + ikx) = qik(x + i−ky) = |ik| · q(x + i−ky) = q(x + i−ky), 1 P3 k −k 2 ∀ k = 0,..., 3, so if we go back to (17) we now have φ(y, x) = 4 k=0 i q(x + i y) , and using the notations from Lemma 2 we have 1 X 1 X φ(y, x) = ζq(x + ζy¯ )2 = ζq¯ (x + ζy)2 = φ(x, y).

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    19 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us